SELECTION OF METHODS OF CARRYING OUT FLOOR PLATE BEKESTING WORK WITH COST COMPARISON - Agriansyah, Eza; Suryo, Eko Andi Suryo; Arifi, Eva (Applied Research on Civil Engineering and Environment (ARCEE), 2024)
The process of developing an area can begin with infrastructure development, where one example of such infrastructure is a building that has various functions. The Surabaya City X building construction project is one of the objects that will be studied in this study. This project has an estimated value of Rp183.000.000.000.00. With a project value of that size, this study aims to choose alternative materials for floor slab formwork work. Floor plate formwork work is one type of work that results in the waste of material used for formwork. Formwork planning requires consideration of using a method or methods to make it easier and cheaper, especially for buildings that are the same shape as the previous building and are of the same size. Conventional floor plate formwork materials are wood, multiplex, and nails; alternative choices are conventional formwork, semi-system formwork, full-system formwork, and bondek plate formwork. The results of this study indicate that when initially analyzed using conventional formwork, it costs Rp6.421.406.646; when using alternative semi-system formwork, it costs Rp6.002.969.805; using full system formwork costs Rp5.530.690.993; and if using bondek plate formwork, it costs Rp6.116.119.937.